2004
DOI: 10.1271/bbb.68.2155
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Resistant Starch Alters the Characteristics of Colonic Mucosa and Exerts a Protective Effect on Trinitrobenzene Sulfonic Acid-induced Colitis in Rats

Abstract: The protective effect of a dietary high-amylose cornstarch (HAS) against trinitrobenzene sulfonic acid (TNBS)-induced colitis was examined in rats. Rats were fed a HAS-free basal diet or, a 15% or 30% HAS supplemented diet for 10 d, and then received intracolonic TNBS to induce colitis and fed the respective diets for a further 8 d. HAS ingestion significantly protected colonic injuries as evidenced by lower colonic myeloperoxidase activity. Rats fed the HAS diet showed greater cecal short-chain fatty acid (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 39 publications
2
27
0
1
Order By: Relevance
“…Enrichment in A. mucinphila was also recently reported for genetically obese ( ob/ob ) mice fed prebiotic carbohydrates (Everard et al ., ). These bacteria might have benefited from increases in cecal mucin production induced by the dietary carbohydrates (Morita et al ., ). Moreover, different Bifidobacterium species were found in mice fed HAM‐RS2.…”
Section: Discussionmentioning
confidence: 97%
“…Enrichment in A. mucinphila was also recently reported for genetically obese ( ob/ob ) mice fed prebiotic carbohydrates (Everard et al ., ). These bacteria might have benefited from increases in cecal mucin production induced by the dietary carbohydrates (Morita et al ., ). Moreover, different Bifidobacterium species were found in mice fed HAM‐RS2.…”
Section: Discussionmentioning
confidence: 97%
“…The protection afforded by fiber and resistant starch in experimental colitis are thought to be dependent on SCFA production (Ito et al, 2009; Morita et al, 2004; Videla et al, 2001), and administration of exogenous butyrate promotes resistance to experimental colitis (Cresci et al, 2013; Leonel et al, 2013). Studies investigating dysbiosis in inflammatory bowel disease identified reduced abundance of butyrate-producing organisms (e.g., certain Roseburia and Faecalibacterium genera) and lower concentrations of butyrate associated with disease (Machiels et al, 2013; Eeckhaut et al, 2013; Sokol et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Ichikawa et al 15) have demonstrated that an oral or rectal administration of SCFA (a mixture of acetic acid, propionic acid and butyric acid) stimulated gut epithelial cell proliferation. Morita et al 16) have reported that mucin production in the gut may be stimulated by SCFA. Butyrate has been found to enhance the cytotoxic activity of natural killer cells and to increase the density of splenic T-helper cells.…”
Section: Discussionmentioning
confidence: 99%